دراسة تحليلية للرعاية اللاحقة للأحداث المنحرفين وتحقيق تكيفهم الاجتماعي - بوكبشة, جمعية (جامعة الوادي - University of Eloued, 2022)
أصبحت الجرائم بكل أنواعها حديث الساعة بتعدد وسائلها ومرتكبيها، خاصة ونحن في عصر عمّ فيه الغزو الالكتروني، أي مع ظهور وسائل التواصل الاجتماعي التي زادت في نسبة ارتكاب الجرائم بطرق فردية و جماعية منظمة وغير منظمة، وتعتبر الفئة الأقل من 18 سنة هي الفئة أكثر تضررا وارتكابا لهذه الجرائم(الجانحين)، وللحد من انتشار هذه الجرائم نجد ما يسمى بالرعاية اللاحقة حتى لا يحدث العود الى الجرم. إذ تعتبر الرعاية اللاحقة من أهم المسائل التي يعيرها الأخصائيون اهتماماتهم حتى لا يحدث العود للجرم خاصة الجانحين الذين هم عرضة للعود، لذلك أبينا في هذه المقال توضيح أهم مزايا هذه الفئة والعوامل المؤدية للجنوح مع التطرق لأهم البرامج العلاجية للرعاية اللاحقة لهذه الفئة التي ينتمي إليها شريحة معتبرة من المجتمع وتمثله، كما أردنا توضيح دور الأخصائي الاجتماعي والنفسي في الرعاية اللاحقة للجانحين وتوضيح أهم الأسباب التي تؤول دون ذلك، وصفا وتحليلا والوقوف على أنجع الطرق لذلك لتكيفه بسهولة وبيئته الاجتماعية. Abstract:As crimes of all kinds have become modern times with multiple means and perpetrators, especially in the era of The cyber-attack prevailed, that is, with the emergence of social media, which increased the rate of committing crimes in organized and unorganized individual and collective ways, and the group under 18 years of age is considered the most affected and perpetrated by these crimes (delinquents), and to limit the spread of these crimes we find the so-called Follow-up care so that recidivism does not occur. Aftercare is one of the most important issues that specialists pay attention to so that recidivism does not occur, especially delinquents who are prone to recurrence. Therefore, in this article, we have clarified the most important advantages of this category and the factors leading to delinquency, with reference to the most important treatment programs for the aftercare of this category, to which a significant segment belongs. We also wanted to clarify the role of the social and psychological specialist in the aftercare of delinquents and to clarify the most important reasons that lead to this, describing and analyzing and identifying the most effective ways for this to easily adapt and social environment.
مقال
Keywords: الرعاية اللاحقة ; الجانحين ; البيئة الاجتماعية ; التكيف ; الاخصائي الاجتماعي; aftercare ; delinquents ; social environment ; adaptation ; social worker